(untitled) (Cadernos de Sociomuseologia, 2021)
This paper is about issues in museum education, starting from the discussion: how to discuss about indigenous histories and cultures with young children in a museum? How has this subject been dealt with? The expographic gaps are here used as the main setting to think over methodologies that help to talk about these questions. We will seek ways to understand how indigenous cultures have been represented and which points of view may help us to widen the mediations targeted to a child audience. Therefore, based on authors that discuss childhood, education and museum education, we think about potential and essential overlaps between mediation, children, and indigenous cultures and histories. key words: Indigenous Histories and Cultures; Children; Museum Education